Copper-catalyzed N-thioetherification of sulfoximines using disulfides. Issue 80 (15th September 2016) - Zhu, Hui; Yu, Jin-Tao; Cheng, Jiang
Abstract : A novel copper-catalyzed N -thioetherification of sulfoximines under mild reaction conditions was developed using readily available disulfides as the sulfur source. Abstract : A novel copper-catalyzed N -thioetherification of sulfoximines under mild reaction conditions was developed. In this procedure, the N–S bond formation was achieved using readily available disulfides as the sulfur source.